Chemical bath deposition of aluminum doped zinc sulfide thin films using non-toxic complexing agent: Effect of aluminum doping on optical and electrical properties - Kazi Hanium Maria; P. Sultana; M. B. Asfia (AIP Advances, 2020)
Zinc sulfide (ZnS) and aluminum doped zinc sulfide (ZnS:Al) thin films have been prepared by chemical bath deposition onto glass substrates at 85 °C using non-toxic complexing agents by varying the Al concentration between 0 wt. % and 18 wt. %. The ZnS and ZnS:Al thin films exhibited a hexagonal wurtzite crystal structure and showed (008) preferential orientation. The Field Emission Scanning Electron Microscope (FESEM) images of the film showed that the glass substrate was nicely covered by compact and dense mosaic like nanostructures. The elemental composition of ZnS and ZnS:Al thin films was measured by energy dispersive x-ray spectroscopy. X-ray photoelectron spectroscopy (XPS) demonstrates the doping of Al into ZnS. From the XPS spectra, the binding energy (BE) values were observed to shift toward the lower BE side for increasing aluminum content. Raman spectra were obtained for the undoped and Al doped ZnS films, which exhibit first-order phonon modes at 328.33 cm−1 and 341.66 cm−1 for the A1/E1 longitudinal optical phonons, and the bands at 253.33 cm−1 and 263.33 cm−1 revealed longitudinal optical phonon–plasmon coupled modes. UV–visible spectrophotometric measurement showed that approximately 70%–80% transmission happened in the visible to near infrared region, with a direct allowed bandgap in the range of 3.52 eV–3.76 eV. A maximum transmittance of 80% was observed for 6 wt. % Al doped ZnS thin films, and the absorption edge shifted toward the blue spectrum region. ZnS and ZnS:Al thin films showed n-type electrical conductivity with carrier concentrations varying from 1.55 × 1017/cm3 to 3.13 × 1017/cm3. Resistivity of the ZnS:Al thin films was decreased with the increase in Al concentration.